The design and evaluation of a culturally adaptive approach to teamwork systems within an education context - Shishah, Wesam (2017)
Educators within higher education and online course designers face a significant challenge when working within multicultural teams. In current user interfaces, the ‘one size fits all’ approach is a critical limitation of online systems, because cultural differences in design are ignored. This thesis addresses these issues through the design and evaluation of an adaptive approach that is based upon individual differences in the cultural dimension (Individualism and Collectivism). In this research, the design strategies developed for teamwork activities are culturally relevant, as well as being effective and original. Two versions of the IdeasRoom system are designed and presented in this study. One version will appeal more to individualist users (IND version), whilst the second version will appeal more to collectivist users (COL version). Both qualitative and quantitative measures were deployed in order to evaluate the two versions for both individualist users and collectivist users, and include: students’ perceptions of free-riding behaviour, perceptions of fairness toward assessment in teamwork, participation in teamwork, satisfaction with teamwork, perceived usability and preference of design. The findings of this study reveal that students demonstrate greater positive reactions to the system version that recognises their cultural background. In addition, the findings suggest that current team working systems used in a number of educational institutions should consider both collectivist and individualist approaches. Evidence provided in this study emphasises the need for adaptation and personalisation approaches to meet the cultural inclinations of students working within educational teamwork learning systems.